Persepsi Siswa Kelas XI Akuntansi terhadap Profesionalisme Guru Pendidikan Agama Islam dalam Penerapan Metode Pengajaran di SMK Negeri 1 Kota Sorong. - Niken Armila; Umar Sulaiman (Al-Fikr: Jurnal Pendidikan Islam, 2017)
This study titled "Perception of Class XI Accounting Students Against Professionalism of Islamic Religious Education in the Application of Teaching Methods in SMK Negeri 1 Kota Sorong" reasons the authors are interested in the title above because of the low understanding of students about the understanding of methods and the lack of professional attitude of PAI teachers at SMK Negeri 1 Sorong City. This research is motivated because not least the teacher's priority scale in teaching is the activity of the teacher itself, even though the real learning is active students in every process of teaching and learning activities. In addition, students' perceptions are not good towards the professionalism of teachers in carrying out their duties and responsibilities at school, one of which is in the application of teaching methods in class so that students are able to understand learning material easily. This type of research is qualitative research with descriptive analysis research. Data collection techniques were obtained by using: 1) interview, namely knowing students' perceptions directly and knowing the methods used by teachers in the classroom. 2) Documentation is in the form of data about the school and documentation throughout the research. The results showed that the XI grade accounting students of SMK Negeri 1 Sorong City had a good perception of the professionalism of Islamic religious education teachers being classified as good.